1998
DOI: 10.1016/s0168-8278(98)80603-x
|View full text |Cite
|
Sign up to set email alerts
|

Transmission of hepatitis C virus infection to tree shrews

Abstract: Although hepatitis C virus (HCV) infection can be reproduced in chimpanzees, these animals are rare and expensive. Tree shrews (tupaias) are small animals, closely related to primates, which adapt easily to a laboratory environment. In this work we have investigated the susceptibility of Tupaia belangeri chinensis to HCV infection. Tupaias caught in the wild in Yunnan (China) were inoculated in China with HCV genotype 1b (study A) and in Spain with a mixture of genotypes 1b, 1a, and 3 (study B). In study B tup… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
10
0

Year Published

2001
2001
2018
2018

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 9 publications
1
10
0
Order By: Relevance
“…Therefore, a single-mutation Leu186F in rat CD81 might suffice HCV permissiveness. The Chinese tree shrew (Tupaia) was previously found permissive for HCV entry, and Tupaia CD81 binds E2 at a comparable level as hCD81 (36). These results agree with our guideline that Tupaia CD81 contains Phe186 and an 188E-196D pair just like hCD81.…”
Section: Discussionsupporting
confidence: 91%
“…Therefore, a single-mutation Leu186F in rat CD81 might suffice HCV permissiveness. The Chinese tree shrew (Tupaia) was previously found permissive for HCV entry, and Tupaia CD81 binds E2 at a comparable level as hCD81 (36). These results agree with our guideline that Tupaia CD81 contains Phe186 and an 188E-196D pair just like hCD81.…”
Section: Discussionsupporting
confidence: 91%
“…T UPAIA (TUPAIA BELANGERI chinensis), a small primate resembling the squirrel, has been reported to be susceptible to hepatitis B virus (HBV) infection in 1996, 3 and was used for the study of HCV infection. 7 However, only a quarter of inoculated individuals con-tracted HCV infection, and developed only a transient or intermittent viremia with low viral loads. Another study group reported on the usefulness of how a primary culture of hepatocytes from the liver of Tupaia can be infected with serum-or plasma-derived HCV from infected humans, as measured by de novo synthesis of HCV RNA, analysis of viral quasispecies evolution, and detection of viral proteins.…”
Section: The Small Primates Modelmentioning
confidence: 99%
“…After whole-body irradiation, the efficiency of infection in the tree shrews may be increased. These animals may serve as an in vivo system for culturing human HCV and addressing pathophysiological and therapeutic issues of HCV infection [52]. Currently, an animal model for HCV-associated HCC has not been established in the tree shrews yet.…”
Section: Virus Hepatitis Modelmentioning
confidence: 99%